The effect of menthol rinsing before intermittent exercise on physiological, physical, and thermo-behavioral responses of male football referees in hot and humid environment - Roriz, Maria; Brito, João; Teixeira, Filipe J.; Spyrou, Konstantinos; Teixeira, Vitor Hugo (Frontiers in Sports and Active Living, 2024)
Introduction In the current experiment, we aimed to evaluate whether eliciting pre-exercise non-thermal cooling sensations would alter perceptual measures, and physical and physiological responses in football referees. Methods Nine highly trained male football referees undertook two 45-minute intermittent exercise protocols in hot and humid conditions (34.2 ± 0.6°C, 62.5 ± 1.0% relative humidity). In a randomized counterbalanced crossover design, 1 of 2 beverages were given before the warm-up: a 0.01% menthol solution or a placebo noncaloric solution. Physical performance was quantified as total distance covered in each of the three 15-minute exercise blocks. Core temperature, heart rate, thermal sensation and thermal comfort were measured at rest and after each exercise block. Results No changes were observed between trials and over time for distance covered. No main effect of mouth rinse was observed for core temperature and heart rate, but both increased over time in all conditions (P < 0.001). Thermal sensation and thermal comfort were significantly improved with menthol after mouth-rinsing (P < 0.05), but with no differences at any other time-point. Discussion These results indicate that non-thermal cooling oral stimuli provide immediate behavioral changes but may not influence physiological or physical responses in football referees, during intermittent exercise in hot and humid environments. Clinical Trial Registration www.clinicaltrials.gov, identifier NCT05632692.